2014
DOI: 10.3171/2013.11.focus13487
|View full text |Cite
|
Sign up to set email alerts
|

Is fluorescein-guided technique able to help in resection of high-grade gliomas?

Abstract: Object Fluorescein, a dye that is widely used as a fluorescent tracer, accumulates in cerebral areas where the blood-brain barrier is damaged. This quality makes it an ideal dye for the intraoperative visualization of high-grade gliomas (HGGs). The authors report their experience with a new fluorescein-guided technique for the resection of HGGs using a dedicated filter on the surgical microscope. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(129 citation statements)
references
References 33 publications
(37 reference statements)
4
114
0
2
Order By: Relevance
“…1,9 However, small study groups have offered limited evidence of the added utility of fluorescein guidance, and rigorous assessment of fluorescein as a marker for tumor pathology in regions beyond MRI contrast enhancement has not been performed. 2,9 In the present study, we evaluate the utility of intraoperative fluorescein imaging for identification of neoplastic tissue, present analytical methods for robust quantification of fluorescein intensity, and assess the correlation of fluorescein staining with histopathological alteration in radiographically localized biopsies, especially as it pertains to regions of nonenhancing tumor.…”
Section: 27mentioning
confidence: 99%
“…1,9 However, small study groups have offered limited evidence of the added utility of fluorescein guidance, and rigorous assessment of fluorescein as a marker for tumor pathology in regions beyond MRI contrast enhancement has not been performed. 2,9 In the present study, we evaluate the utility of intraoperative fluorescein imaging for identification of neoplastic tissue, present analytical methods for robust quantification of fluorescein intensity, and assess the correlation of fluorescein staining with histopathological alteration in radiographically localized biopsies, especially as it pertains to regions of nonenhancing tumor.…”
Section: 27mentioning
confidence: 99%
“…2011-002527-18). The protocol and preliminary data on extent of resection, as derived from study design, were reported previously (18,19).…”
Section: Patientsmentioning
confidence: 99%
“…When intravenously injected, SF has the capability to selectively accumulate in brain areas with altered blood-brain barrier (BBB), related to the presence of high-density HGG tumor cells (16). It has been shown that SF improves tumor visualization, either with white light illumination and, more precisely, by the aid of a specific filter in the surgical microscope (17)(18)(19)(20)(21). In 2011, our group started the first prospective phase II trial (FLUOGLIO) with minimax Simon 2-stage design, to evaluate the safety and efficacy of fluorescein-guided resection of HGGs by the use of a dedicated fluorescence filter in the surgical microscope.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescein sodium, a small organic molecule that fluoresces a yellow-green color in white light, is an exogenous contrast agent that was first introduced in tumor resection surgery in 1948. It has been used extensively for the past couple of decades for brain tumor identification during open biopsies and retinal angiography [8,13]. Similarly to 5-ALA, fluorescein sodium can target malignant tissue because it is permeable to regions of the brain where the blood-brain barrier is distorted from tumor angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, neurosurgeons can utilize intraoperative confocal endomicroscopes with fluorescein sodium, 5-ALA, and indocyanine green to enhance the fluorescent intensity, which improves one's ability to delineate tumor margins. In a Phase II prospective study on the efficacy of fluorescein sodium in conjunction with a surgical microscope fitted with filters to emphasize fluorescing tissue for fluorescence-guided surgery on 20 glioma patients, 80% of patients had their tumors completely removed, and six month progression-free survival was 71.4% [13]. Thirty-six biopsies of fluorescing and non-fluorescing samples (18 samples for each group) taken at tumor margins were evaluated by immunohistochemical analysis and reflected robust results (94% sensitivity and 89.5% specificity).…”
Section: Introductionmentioning
confidence: 99%